Aplikasi Pengecekan Alat Pemadam Api Ringan (APAR) Berbasis Android Pada PT. XYZ Di Bekasi - Endah Yaodah Kodratillah; Nisa Nurhidayanti; Ana Fitrotun Nisa (Teknik Informatika, Universitas Pelita Bangsa, 2022)
APAR has a very important effect for handling small / light fires in a place. PT. XYZ in Bekasi is an industry that is engaged in food production, so it takes a lot of fire extinguishers to meet government regulations (PERMENAKER). Due to the large number of fire extinguishers currently available, a system/application is needed to assist during the APAR checking process and data management based on Android based APAR checking results. So that the process can be carried out more quickly, precisely, and will get information on APAR that are nearing expiry/APAR which needs to be replaced with new APAR contents (refill APAR). The methodology used to develop this system uses the waterfall method and the PHP programming language. The result of developing this application is an APAR checking application/system that is useful for minimizing officer errors in writing, searching for data from APAR checking results quickly and accurately, and providing information to officers about APARs that will expire/need to be refilled. The application can be accessed anywhere and anytime via android/smartphone. Keywords: Checking APAR, Android, Waterfall, PHP, Expired APAR.